2020
DOI: 10.2147/ott.s232718
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antitumor Effect of miR-1294/Pyruvate Kinase M2 Signaling Cascade in Osteosarcoma Cells</p>

Abstract: Background: MicroRNAs (miRNAs) can act as negative regulators of gene expression, and play a crucial role in cancer progression. The aim of this study was to investigate the role of miR-1294/pyruvate kinase M2 (PKM2) axis in osteosarcoma cells in vitro and in vivo. Methods: The function of miR-1294 and its association with PKM2 in osteosarcoma cells were studied by real-time PCR, CCK-8, Western blot, scratch test, transwell assay, flow cytometry, and dual-luciferase reporter assays. The effect of miR-1294 on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…PKM2 synthetic peptide aptamers and small molecules targeting PKM2 have also been shown to reduce the growth of tumor cells [174,202], indicating the pathologic role of the PKM2 isoform in cancer cells. Overexpression of miR-1294, which inhibits PKM2 expression, inhibits cell proliferation, migration, and invasion, and induces apoptosis in osteosarcoma cells [203]; however, miRs have many targets and this miR intervention would not selectively target PKM2. Increased expression of the PKM2 tetramer, which is the active form of PKM2, inhibits glycolysis and promotes glucose oxidation [204].…”
Section: Inhibition Of Pkm2mentioning
confidence: 99%
“…PKM2 synthetic peptide aptamers and small molecules targeting PKM2 have also been shown to reduce the growth of tumor cells [174,202], indicating the pathologic role of the PKM2 isoform in cancer cells. Overexpression of miR-1294, which inhibits PKM2 expression, inhibits cell proliferation, migration, and invasion, and induces apoptosis in osteosarcoma cells [203]; however, miRs have many targets and this miR intervention would not selectively target PKM2. Increased expression of the PKM2 tetramer, which is the active form of PKM2, inhibits glycolysis and promotes glucose oxidation [204].…”
Section: Inhibition Of Pkm2mentioning
confidence: 99%
“…Previous studies have shown that PKM2 is correlated with the Enneking stage and distant metastasis in OS, and it has been identified as an independent prognostic factor for lethal disease (13)(14)(15)18,42). These studies revealed that PKM2 may represent a new therapeutic target for OS.…”
Section: Discussionmentioning
confidence: 87%
“…Another study confirmed that metformin increased the sensitivity of OS stem cells to cisplatin by inhibiting the expression of PKM2 (14). The miR-1294/PKM2 signaling cascade plays important roles in the regulation of OS progression (15). Through direct binding to specific sequence element(s), RNA binding proteins (RBPs) play a pivotal role in co-and post-transcriptional RNA regulatory events (16).…”
Section: Lncccat1 Interaction Protein Pkm2 Upregulates Srebp2 Phospho...mentioning
confidence: 88%
See 1 more Smart Citation
“…miR-1294 was predicted to be a cotarget for circSHKBP1 and PKM2 through an online database and article. 21 miR-1294 was found to be downregulated, while PKM2 was upregulated in 30 NSCLC tissues with high levels of circSHKBP1 (Figures S3A and S3B). Furthermore, we found that the expression of miR-1294 was negatively associated with the expression of circSHKBP1, and that the expression of PKM2 was positively associated with the expression of circSHKBP1 (Figures S3C and S3D).…”
Section: Exosomal Circshkbp1 Enhances the Stemness Of Nsclc Cells In ...mentioning
confidence: 98%